2021
DOI: 10.1038/s41598-021-92875-9
|View full text |Cite
|
Sign up to set email alerts
|

Combination immunotherapy with two attenuated Listeria strains carrying shuffled HPV-16 E6E7 protein causes tumor regression in a mouse tumor model

Abstract: Cervical cancer continues to impose a heavy burden worldwide, and human papilloma virus (HPV) infection, especially persistent infection with type 16 (HPV-16), is known to be the primary etiological factor. Therapeutic vaccines are urgently needed because prophylactic vaccines are ineffective at clearing pre-existing HPV infection. Here, two recombinant Listeria strains (LMΔ-E6E7 & LIΔ-E6E7) with deletions of the actA and plcB genes, expressing the shuffled HPV-16 E6E7 protein were constructed. The strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…We confirmed that combination therapy with two different recombinant Listeria strains (LM and LI) has a more satisfactory anti‐tumour effect than the administration of a single strain (Su et al, 2021 ). This suggests that both LI and LM hold strong potential for the development of Listeria ‐vectored vaccines.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…We confirmed that combination therapy with two different recombinant Listeria strains (LM and LI) has a more satisfactory anti‐tumour effect than the administration of a single strain (Su et al, 2021 ). This suggests that both LI and LM hold strong potential for the development of Listeria ‐vectored vaccines.…”
Section: Discussionsupporting
confidence: 75%
“…In future applications, to maximize the protective efficacy of LIΔdd:dal vectored vaccines, the immunization strategy may need to be optimized and can be optimized by double boost immunization (Pownall et al, 2021) or co-immunization with other type of vaccine. Besides, our previous research had confirmed that the sequential immunization with different Listeria strains vectored vaccine candidates will significantly enhance the immunotherapeutic effect (Su et al, 2021). So the protective efficacy could also be enhanced by co-immunization with other vectored vaccine such as LMΔdd:dal vectored vaccine.…”
Section: Listeria Ivanovii Balanced-lethal Systemmentioning
confidence: 90%
See 1 more Smart Citation
“…Bacterial vectors‐based vaccines : Listeria and Lactobacillus are the most widely studied vectors 308–310 . Listeria‐based vaccines ADXS11‐001 have undergone phase I/II clinical to assess their efficacy and safety in HPV+ cervical cancer (NCT02164461 and NCT01266460).…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Therefore, there are still gaps in the research on the immune regulation mechanism of cervical cancer tumor vaccines in tumor prevention. We have successfully constructed two Listeria -vector cervical cancer vaccine candidate strains, LM∆E6E7 and LI∆E6E7, and confirmed that combined immunotherapy with these two vaccine candidate strains could effectively inhibit tumor progression [ 19 ]. Therefore, in this study we aimed to investigate the role of TAAs-specific Tm-cell responses induced by preimmunizing with LM∆E6E7 and LI∆E6E7 in the tumor prevention and the potential antitumor mechanism.…”
Section: Introductionmentioning
confidence: 99%